A little thing called life : on loving Elvis Presley, Bruce Jenner, and songs in between - Thompson, Linda, 1950- (Dey St., 2016)
Songwriter and actress Linda Thompson breaks her silence for the first time to share the extraordinary story of her life, career, and her epic romances with two of the most celebrated, yet enigmatic, modern American superstars--Elvis Presley and Bruce Jenner. Contains lyrics to many of her songs.